2011
DOI: 10.1039/c0nr00610f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous synthesis of ZnTe/dendrimer nanocomposites and their antimicrobial activity: implications in therapeutics

Abstract: The present strategy proposes a simple and single step aqueous route for synthesizing stable, fluorescent ZnTe/dendrimer nanocomposites with varying dendrimer terminal groups. In these hybrid materials, the fluorescence of the semiconductor combines with the biomimetic properties of the dendrimer making them suitable for various biomedical applications. The ZnTe nanocomposites thus obtained demonstrate bactericidal activity against enteropathogenic bacteria without having toxic effects on the human erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…FT-IR, 1 This result verifies that LDH-CA was successfully formed in the hybrid PI composites by the thermal imidization techniques (Fig. 3c-3e).…”
Section: Ft-ir and 1 H-nmr Studysupporting
confidence: 74%
“…FT-IR, 1 This result verifies that LDH-CA was successfully formed in the hybrid PI composites by the thermal imidization techniques (Fig. 3c-3e).…”
Section: Ft-ir and 1 H-nmr Studysupporting
confidence: 74%
“…It has been reported that pure G4-PAMAM dendrimers exhibit some antimicrobial activity against E. coli at higher ISRN Nanomaterials concentrations, which is due to penetration of the cell membrane by PAMAM dendrimers containing primary amine surface functional groups [31]. One may speculate that the dendrimer solution is adding to (or even dominating) the antimicrobial effect of the formed Ni nanoparticles.…”
Section: Antimicrobial Activity Of Dendrimer-encapsulated Ni(0)mentioning
confidence: 99%
“…That is, Ni nanoparticles interact with the building components of the outer layer of the bacteria disrupting the cell wall and finally preventing further bacteria, and it has been suggested that antimicrobial activity should increase depending on particle size. Other reports have indicated that the larger surface-area-to-volume ratio exhibited by the smaller particles along with an increased penetrating ability will result in particles with increased effective binding on the outer membrane and cell membranes of organisms [31]. Hence, given the smaller sizes of the Ni particles formed here (ca.…”
Section: Antimicrobial Activity Of Dendrimer-encapsulated Ni(0)mentioning
confidence: 99%
“…Chemical modifications of PAMAM-NH 2 dendrimers were demonstrated to reduce their toxicities, but these modifications simultaneously reduced the antibacterial activities of the PAMAM-NH 2 dendrimers (11,16). To date, antibacterial research on PAMAM-NH 2 dendrimers has been limited to topical (17)(18)(19) and drug carrier applications (20)(21)(22). Insufficient data are available to determine whether PAMAM-NH 2 dendrimers could be used systemically as antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%